The Study of Analgesic Effect of Hydroalcoholilc Extract of vitis vinifsraseedon Rat by Formalin TEST - Ardeshir Arzi; Ali Asgar Hemati; Mohammad Moussen Mehrabi; Amir Siahpush; Zahra Nazari (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Background and Objective: Due to the increased role of medicinal plants in therapy, the aim of this research was to study and compare the analgesic effect of hydroalcoholic extract of the seeds of Vitis vinifera with morphine and aspirin as a common analgesic.Subjects and Methods: In this study, the hydroalcoholic extract of Vitis vinifera seed was prepared by maceration method. This study was done on male Wistar rat species. The animals were divided into 7 groups (n= 9): Negative control group received a single dose of (5mg/kg of serum physiology), two positive control groups (one group 2.5mg/kg of morphine and another 300mg/kg of aspirin), 4 treatment groups (100,200,400and 800 mg/kg) of hydroalcoholic extract of the seeds of Vitis vinifera via intraperitoneally. In this study the analgesic effect was investigated by using formalin test.Results: The results indicated that the analgesic effect of 400mg/kg of extract on the phase 1 of pain was more than the aspirin and less than the morphine. Its chronic analgesic effect on phase 2 of pain was less than morphine but there weren't any significant differences with those of the aspirin.Conclusion: The results indicated that the hydroalcoholic extract of Vitis vinefera seed contains analgesic effect in both acute and chronic phases of pain. This can probably be due to the influence of the antioxidants of this extract.